RUMAH GAYA ARSITEKTUR MINIMALlS di YOGYAKARTA . - Bambang Sugestiyadi (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2006)
ABSTRACTYogyakarta could be the mirror of "Nusantara" since it had beenaccumulated with people from all around the Nusantara for education. Itgradually grow into semi metropolis city, where new physical facilitiesdeveloped. There for physical facilities are needed. This research wasconducted to know the minimalism architecture style implemented inhouse development in Yogyakarta.The research was' carried out on qualitative design. Data iscollected through observation, visualization, skates maker, photodocumentation and deeply interview. Relevant documentation from otherconnected departments was taken. Data is analyzed with inductivemethod: it does not mean to reveal hypothesis but it is focused to makean abstract. Triangulation was conducted to test data validity.The results showed that: (a) House and housing developmentuntil 2004 decade still dominated by Mediteran Style, Tropical HouseStyle and Classical House Style with ornaments, (b) The MinimalismHouse Style in architecture focuses on essential and functional aspects.The Minimalism Style dominated by basic geometrical forms withoutornament or decoration; It began to grow since 2004 to 2006, in SlemanRegency, Yogyakarta.Keywords: Architecture Style, Development, MinimalismArchitecture Style.